COMPARATIVE ANALYSIS OF ADVERBS IN UZBEK AND ENGLISH LANGUAGES (Лучшие интеллектуальные исследования, 2025)
Annotation. This article provides a comparative analysis of adverbs in the Uzbek and English languages, focusing on their morphological, syntactic, and semantic characteristics. The study examines how adverbs function in both languages, their formation patterns, and their role in sentence structure. Special attention is given to similarities and differences in the use of adverbs, considering their position, modification abilities, and degrees of comparison. The findings contribute to a better understanding of cross-linguistic variations and help in translation and language learning processes.Annotatsiya. Mazkur maqolada o‘zbek va ingliz tillaridagi ravishlarning qiyosiy tahlili yoritiladi. Tadqiqot ravishlarning morfologik, sintaktik va semantik xususiyatlarini o‘rganishga qaratilgan bo‘lib, ularning hosil qilinishi, gap tarkibidagi roli va grammatik tuzilishdagi o‘rni ko‘rib chiqiladi. Shuningdek, ravishlarning o‘zaro o‘xshashliklari va farqlari, ularning darajalari va o‘zgarish xususiyatlari tahlil qilinadi. Ushbu tadqiqot natijalari tarjima jarayoni va til o‘rganishda muhim ahamiyat kasb etadi. Аннотация. В данной статье проводится сравнительный анализ наречий в узбекском и английском языках, уделяя внимание их морфологическим, синтаксическим и семантическим особенностям. Исследование рассматривает функции наречий в обоих языках, их образование и роль в структуре предложения. Особое внимание уделяется сходствам и различиям в использовании наречий, включая их позицию, способность к модификации и степени сравнения. Полученные результаты способствуют лучшему пониманию межъязыковых различий и помогают в переводе и изучении языков.